« Le personnel est académique ».Pour une subversion féministe de l’université, de la pédagogie à l’institution - Vanina Mozziconacci (Genre, Sexualité et Société)
This paper analyzes three kinds of feminist subversion of the university. Each subversion instantiates the rallying slogan “The personal is political” in the academic context, be it in its pedagogic, scientific or institutional dimensions. From an ethical perspective, “the personal” can be considered synonymous with “personal feelings” as it is taken into account in feminist pedagogies. Considering “personal experiences” is also an essential epistemological issue in both feminist scholarship and feminist activism, in relation with consciousness raising. Finally, to acknowledge “the private” implies to take into account the care work done in the domestic sphere and cannot go without a transformation of academic culture, in order to make room for the (so-called) reproductive labor in universities.